2020
DOI: 10.1002/cncr.33387
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and associations with structural brain networks, endocrine status, and risk genotypes in patients with newly diagnosed prostate cancer referred to androgen‐deprivation therapy

Abstract: Background Evidence suggests that patients with prostate cancer (PCPs) receiving androgen‐deprivation therapy (ADT) are at risk for cognitive impairment. Research with other populations with cancer indicates that cognitive impairment may also occur before systemic treatment. The authors assessed cognitive impairment in untreated PCPs referred to ADT and explored associations with structural brain networks, endocrine status, and selected genotypes. Methods Forty untreated PCPs and 27 healthy controls (HCs) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Second, working memory represents one aspect of cognitive functions. Studies are needed to employ a more comprehensive battery of neuropsychological tests and other neural metrics to fully investigate potential cognitive dysfunction in prostate cancer patients receiving ADT 65 . Finally, as patients may undergo ADT for a longer duration, the current findings should be considered as specific to patients with only 6 months of exposure to ADT.…”
Section: Discussionmentioning
confidence: 99%
“…Second, working memory represents one aspect of cognitive functions. Studies are needed to employ a more comprehensive battery of neuropsychological tests and other neural metrics to fully investigate potential cognitive dysfunction in prostate cancer patients receiving ADT 65 . Finally, as patients may undergo ADT for a longer duration, the current findings should be considered as specific to patients with only 6 months of exposure to ADT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have previously reported an association between high CAG repeat length and better verbal memory performance at the baseline assessment of the present TCP sample. 3 This finding, however, was in contrast with previous studies with prostate cancer patients 30 and healthy older men 29 reporting associations between high CAG repeat length and poorer cognitive functions. Accordingly, given the limited and conflicting evidence, it remains unclear how CAG repeat length might exert an effect on cognitive functions in different populations.…”
Section: Discussionmentioning
confidence: 76%
“…26 Notably, it has also been indicated that CAG repeat length may in itself exert an effect on cognitive functions; however, existing findings have been equivocal. 3,[26][27][28][29][30] Given that only a subgroup of cancer survivors develop CD, it is important to elucidate risk factors, including genetic risk. 1 Previous research has suggested a role for the APOE (e.g., 5,31 ) encoding the glycoprotein apolipoprotein ε, COMT (e.g., 32 ) encoding catechol-O-methyltransferase, and BDNF 1,33 encoding brain-derived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that testosterone levels in the bloodstream may provide neuroprotective effects, as indicated by a direct relationship between testosterone levels and cognitive function. 12 , 65 , 67 , 68 …”
Section: Relationship Between Alzheimer’s and Prostate Cancermentioning
confidence: 99%